2018
DOI: 10.1101/340943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamic neural code of the retina for natural scenes

Abstract: The normal function of the retina is to convey information about natural visual images. It is this visual environment that has driven evolution, and that is clinically relevant. Yet nearly all of our understanding of the neural computations, biological function, and circuit mechanisms of the retina comes in the context of artificially structured stimuli such as flashing spots, moving bars and white noise. It is fundamentally unclear how these artificial stimuli are related to circuit processes engaged under na… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 38 publications
1
40
1
Order By: Relevance
“…Regarding mechanisms, the spatiotemporal linear filter of the LN model is typically interpreted as mapping onto the aggregate sequential mechanisms of phototransduction, signal filtering and transmission through bipolar and amacrine cell pathways, and summation at the ganglion cell, while the nonlinearity is mapped onto the spiking threshold of ganglion cells. Regarding accuracy, while previous studies have found that these simple models can, for some neurons, capture most of the variance of the responses to low-resolution spatiotemporal white noise [9, 12, 20], they do not describe responses to stimuli with more structure such as natural scenes [13, 3033]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding mechanisms, the spatiotemporal linear filter of the LN model is typically interpreted as mapping onto the aggregate sequential mechanisms of phototransduction, signal filtering and transmission through bipolar and amacrine cell pathways, and summation at the ganglion cell, while the nonlinearity is mapped onto the spiking threshold of ganglion cells. Regarding accuracy, while previous studies have found that these simple models can, for some neurons, capture most of the variance of the responses to low-resolution spatiotemporal white noise [9, 12, 20], they do not describe responses to stimuli with more structure such as natural scenes [13, 3033]. …”
Section: Introductionmentioning
confidence: 99%
“…Another common assumption is that the subunit nonlinearities have a particular form, such as quadratic [11, 25] or sigmoidal [44]. Fitting multi-layered models with convolutional filters and fixed nonlinearities has also been successfully used to describe retinal responses to natural scenes [32, 33], although this work maximizes predictive accuracy at the expense of a one-to-one mapping of model components onto retinal circuit elements. Finally, other work focuses on particular ganglion cell types with a small number of inputs [22], constrains the input stimulus to a low-dimensional subspace (such as two halves of the receptive field [45]), or constrains the coefficients of receptive fields to be non-negative [46], thus discarding known properties of the inhibitory surround.…”
Section: Introductionmentioning
confidence: 99%
“…Natural scenes have been used for reverse correlation analysis, which generally yielded receptive fields comparable to the ones obtained with white noise stimuli (Ringach et al, 2002;Theunissen et al, 2001;Touryan et al, 2005;Vance et al, 2016;Willmore et al, 2010). On the other hand, a recent study highlights the dynamic nonlinearities during natural scene stimulation in salamander retinal ganglion cells (Maheswaranathan et al, 2019), where white-noise-derived models are not able to explain their data well. Overall, whereas many response properties of cells can be probed with artificial stimuli, the use of natural stimuli can further our understanding of a dynamic neural circuit that has evolved in natural conditions.…”
Section: Ll Open Access Iscience Articlementioning
confidence: 96%
“…proposed a set of computational retinal microcircuits that can be used as basic building blocks for the modelling of different retina mechanisms [30]. Recently, deep convolutional neural networks were shown to capture retinal responses to natural scenes, with results that were close to the variability of the cellular response range [31,32], as well as multitask recurrent neural networks that provided the necessary flexibility to model complex neuronal computations [33].…”
Section: Related Workmentioning
confidence: 99%